Community-Based Education for the Preservation of Topeng Ireng Dance in Transmigrant Area Communities - Putri Dyah Indriyani; Dedy Ary Nugroho; Rusmaniah (Institute of Computer Science (IOCS), 2022)
This study aims to analyze the educational model applied to the Topeng Ireng dance by the transmigrant local community in Dandajaya Village, Rantau Badauh District, Barito Kuala Regency. This research method is descriptive qualitative. The data collection method applied in this research is the method of observation, interviews and documentation. The results obtained in this study are the application of educational methods that are free and hereditary as well as the change of location carried out by the transmigrant area community causing the impact of learning outcomes to be varied and innovative. The Topeng Ireng dance, which is the learning material, is different from the Topeng Ireng dance in its native area. This is because there are developments and variations made by the art community in the area.